γ-SECRETASE INHIBITORS AND MODULATORS FOR ALZHEIMER’S DISEASE - Wolfe, Michael S. (2011)
γ-Secretase is a membrane embedded aspartyl protease complex with presenilin as the catalytic component. Along with β-secretase, this enzyme produces the amyloid β-protein (Aβ) of Alzheimer’s disease (AD) from the amyloid β-protein precursor (APP). Because of its key role in the pathogenesis of AD, γ-secretase has been a prime target for drug discovery, and many inhibitors of this protease have been developed. The therapeutic potential of these inhibitors is virtually negated by the fact that γ-secretase is an essential part of the Notch signaling pathway, rendering the compounds unacceptably toxic upon chronic exposure. However, these compounds have served as useful chemical tools for biological investigations. In contrast, γ-secretase modulators continue to be of keen interest as possible AD therapeutics. These modulators either shift Aβ production to shorter, less pathogenic peptides or inhibit the proteolysis of APP selectively compared to that of Notch. The various chemical types of inhibitors and modulators will be discussed, along with their use as probes for basic biology and their potential as AD therapeutics.